Pengembangan Model Pembelajaran Berbasis Permainan Sirkuit Untuk Meningkatkan Motorik Halus Anak Usia 4-5 Tahun - Arie Paramitha, Made Vina; Sutapa, Panggung (Jurnal Golden Age, 2019)
This study aimed to: (1) develop a circuit-based learning model appropriate to early childhood development, and (2) to know the effectiveness of the application of circuit-based learning model to the children's fine motor at the age of 4-5 years. This type of research is Research and Development. This type of research is research and development (R D). Research subjects in this study were children aged 4-5 years. The technique and instrument of data collection is by using interview, observation sheet and validation sheet or questionnaire. The data analysis technique of effectiveness test used is by nonparametric statistic analysis Wilcoxon test or sign test. The Result of Developing a Game Based Learning Model The Circuit contains steps in which it consists of several game activity postings, and is documented in the form of CDs and instructional instruction manuals. Learning steps consisting of preliminary activities, warm-up activities, core activities (circuit play), and end activities (cooling). The results of validation by experts and also teachers found that the products developed into the category of "good". The development of circuit-based learning model is declared effective in improving children's fine motor